Comprehensive Decision Analysis of Industry 4.0 Virtual Enterprises considering the Personalized Customization Model of Product Life Cycle. (25th February 2022) - Ma, Dongjun
Abstract : In the era of Industry 4.0, various types of information accumulated by enterprises in the production process have become a sea of data. These manufacturing-related data originate from enterprises and are used by enterprises and include not only process data such as documents and pictures but also complex information such as video and sound. Moreover, these data are not only large in quantity and wide in variety but also have the characteristics of fast generation speed and low value density. The model constructed in this paper can be applied to the personalized customization of product life cycle and can help enterprises make comprehensive decision-making. In particular, it can perform intelligent decision analysis under the background of Industry 4.0. In addition, this article combines intelligent algorithms to build an intelligent enterprise comprehensive decision-making system. The experimental research results show that the decision-making system proposed in this paper can play an important role in the comprehensive decision-making of Industry 4.0 enterprises, and this decision-making can be spread throughout the entire life cycle of the product.